2010
DOI: 10.1053/j.gastro.2009.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Loss or Silencing of the PHD1 Prolyl Hydroxylase Protects Livers of Mice Against Ischemia/Reperfusion Injury

Abstract: Loss of PHD1 provided tolerance of hepatocytes to acute hypoxia and protected them against I/R-damage. Short-term inhibition of PHD1 is a novel therapeutic approach to reducing or preventing I/R-induced liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 30 publications
10
101
1
5
Order By: Relevance
“…Pyruvate dehydrogenase kinase 1, a key regulator for glycolysis, did not change in the setting of pMCAO, although it has been established as an important mediator of resistance to muscle and liver ischemia in mice lacking PHD-1 (Aragones et al, 2008;Schneider et al, 2010). However, those tissues have a huge potential in upregulating their gylcolytic metabolism during hypoxia/ischemia, which is not the case for the brain, and it seems unlikely that increased glycolysis is a potential mechanism of PHD/HIF-related neuroprotection.…”
Section: Discussionmentioning
confidence: 93%
“…Pyruvate dehydrogenase kinase 1, a key regulator for glycolysis, did not change in the setting of pMCAO, although it has been established as an important mediator of resistance to muscle and liver ischemia in mice lacking PHD-1 (Aragones et al, 2008;Schneider et al, 2010). However, those tissues have a huge potential in upregulating their gylcolytic metabolism during hypoxia/ischemia, which is not the case for the brain, and it seems unlikely that increased glycolysis is a potential mechanism of PHD/HIF-related neuroprotection.…”
Section: Discussionmentioning
confidence: 93%
“…The generation of PHD knockout mice has been described elsewhere (13,17,18). All animal experiments were approved by the ethical commission of the local government.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Recent studies applying genetic loss-of-function approaches indicated that PHD enzymes carry out specific and nonredundant in vivo functions. Loss of PHD1 specifically alters the mitochondrial energy metabolism of skeletal muscle (12) or liver cells (13), thus increasing their hypoxic survival. Furthermore, loss of PHD1 increases the intestinal barrier function and is protective against experimental colitis (1,14).…”
mentioning
confidence: 99%
“…Schneider et al exposed liver allografts to 90 min of warm ischemia by clamping of the portal vessels with 8 h of reperfusion in PHD1 (À/À) mice (30). The authors demonstrated resistance to ischemia in the PHD1 (À/À) mice as assessed by quantifying apoptosis, necrosis and mouse survival.…”
Section: Livermentioning
confidence: 99%